Effect of medium composition and culture condition on the production of bacteriocin-like inhibitory substances (BLIS) by Lactobacillus paracasei LA07, a strain isolated from budu - Abbasiliasi, Sahar; Ramanan, Ramakrishnan Nagasundara; Tengku Ibrahim, Tengku Azmi; Mustafa, Shuhaimi; Mohamad, Rosfarizan; Mohd Daud, Hassan; Ariff, Arbakariya (Taylor & Francis, 2011)
The effect of medium composition (type and concentration of carbon and nitrogen sources) and culture conditions (pH, aeration and temperature) on the production of bacteriocin-like inhibitory substances (BLIS) by Lactobacillus paracasei LA07 was studied in shake flask culture. The highest BLIS production was obtained from de Man, Rogosa and Sharpe (MRS) broth, which was 4%, 22%, 51% and 63% higher than those obtained in M17 Broth, Tryptic Soy Broth (TSB), Brain Heart Infusion Broth (BHIB) and Nutrient Broth (NB) respectively. The addition of meat extract (5 g/L) and yeast extract (5 g/L) to MRS broth increased further BLIS production by 5% and 8%, respectively. The production of BLIS was further improved by 11% and 13% through the addition of tryptone (3 g/L) and glucose (10 g/L), respectively. The growth of Lb. paracasei LA07 and BLIS production were not significantly affected by agitation, either in anaerobic or in aerobic conditions. The optimum initial pH and temperature for BLIS production by Lb. paracasei LA07 was pH 8.5 and 30 °C, respectively.